Incidence of Phoma leaf spot disease of large cardamom (Amomum subulatum Roxb.) and in vitro evaluation of fungicides against the pathogen - U Gupta, A K Biswas, K A Saju, T N Deka, M R Sudharshan, (Journal of Spices and Aromatic Crops, 2011)
Surveys conducted in 17 locations in North East India indicated that the incidence of Phoma leaf spot disease of large cardamom (Amomum subulatum.) caused by P. hedericola ranged from 5% to 15%. Six fungicides were evaluated in vitro against the pathogen and carbendazim 50WP was significantly effective at allconcentrations (0.05% - 0.15%) tested followed by carbendazim + mancozeb 75WP (0.1% - 0.4%).